The creativity of chemistry education students in the digital age - Setiawan, Nur Candra Eka; Herunata, Herunata; Rosli, Mohd Shafie (Eclética Química, 2025)
The creativity of chemistry education students in the digital era is an exciting topic for discussion, given the critical role of creativity in developing innovations for prospective chemistry teachers. This study explores the creativity of chemistry education students in the digital era. The research method used is descriptive qualitative with data collection techniques through learning with hypothetical deductive learning cycle models, interviews, and observations. The research participants consisted of twenty-nine fifth-semester chemistry education students. The results showed that 70% of chemistry education students were in the creative category, and 30% were in the moderately creative category. This study provides essential information about the creativity of chemistry education students in facing the digital era, as well as challenges and opportunities that must be considered in the development of chemical education innovations in the digital era.